Children’s Perspective and Aspirations on A Green Environment Through Environmental Education - Destria Angelina; Ali Formen; Yuli Kurniawati Sugiyo Pranoto (AL-ISHLAH: Jurnal Pendidikan, 2026)
Environmental degradation and climate change have increased the need for effective environmental education (EE) from early childhood. Although EE is increasingly embedded in early childhood curricula, limited research has explored young children's own perspectives and aspirations regarding what constitutes a green and sustainable environment. This study aimed to explore how children conceptualize a green environment and the aspirations they express for environmental care. A qualitative participatory case study was conducted with 17 children aged 4–6 years from three early childhood education institutions in Semarang, Indonesia. Data were collected through participatory observations, draw-and-tell activities, semi-structured interviews, and document analysis. The data were analyzed using Braun and Clarke's six-phase reflexive thematic analysis and interpreted through the UNESCO–UNEP Environmental Education framework of learning about, in, and for the environment. Five interconnected themes emerged: (1) a clean environment free from waste and flooding; (2) a pollution-free environment that supports healthy living; (3) harmonious coexistence with plants and animals; (4) safe, enjoyable, and disaster-resilient spaces for play; and (5) sustainable everyday practices, including energy conservation and recycling. Children's narratives and drawings revealed that they viewed environmental sustainability through cognitive, emotional, and moral lenses, expressing empathy toward nature and a sense of personal responsibility for environmental stewardship. The findings demonstrate that young children are capable of articulating meaningful environmental perspectives and aspirations. Positioning children as active contributors to environmental education can strengthen participatory, child-centered approaches to Education for Sustainable Development and inform the design of developmentally appropriate environmental learning in early childhood settings.